2019
DOI: 10.7216/1300759920192611401
|View full text |Cite
|
Sign up to set email alerts
|

Partially Transformation of Zinc Nitrate to Zinc Compounds on PVC Nanofibers at

Abstract: Bu makaleye atıf yapmak için (To cite this article):

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The results showed that the composite has a reception capacity of up to 33.82% at a constant frequency. Akgül et al [122] obtained electrospun PVC/zinc nitrate nanofiber aiming to cover draped fabrics where controlled light transmission is required. Zhu et al [61] used PVC nanofiber mats as effective adsorbents for cationic dye removal from an aqueous medium.…”
Section: Other Applicationmentioning
confidence: 99%
“…The results showed that the composite has a reception capacity of up to 33.82% at a constant frequency. Akgül et al [122] obtained electrospun PVC/zinc nitrate nanofiber aiming to cover draped fabrics where controlled light transmission is required. Zhu et al [61] used PVC nanofiber mats as effective adsorbents for cationic dye removal from an aqueous medium.…”
Section: Other Applicationmentioning
confidence: 99%